Exploring How AI, Machine Learning, and Social Media Data Impact Digital Marketing and Consumer Behavior - Istiak, Lazim; Kabir, Ahmed Imran; Fahad , Abdullah Al; Sarker , Jayanta; Queeney , Yeana Anmol; Kazi, Zaheeb Jowad (Electronic Journal of Business and Management, 2025)
This study investigates the transformative role of artificial intelligence (AI) in digital marketing, focusing on its function as a mediating variable that enhances marketing strategies. AI technologies, including predictive analytics and machine learning, enable businesses to deliver personalized user experiences, streamline processes, and gain actionable insights into consumer behavior. The research examines AI’s impact on targeted advertising, consumer behavior, and social media mining, emphasizing its ability to optimize outcomes in digital marketing. A survey of marketing professionals reveals that while direct relationships between consumer behavior, machine learning algorithms, and social media mining with digital marketing are limited, AI significantly enhances their combined effectiveness. By automating tasks, analyzing large datasets, and delivering precision-driven marketing, AI fosters deeper consumer engagement and more resonant campaigns. Despite its contributions, the study acknowledges limitations, including a focus on quantitative data and a restricted sample size, suggesting the need for future research to explore qualitative insights, ethical considerations, and the long-term implications of AI in marketing.